Systematic Understanding of the Function of Public Criminal Prosecution - Meurmishvili, Besik (Journal of Law, 2023)
Public prosecution is one of the necessary and important institutions for effective obstruction of justice. Applying this legal instrument reduces crime, eliminates fear of crime, and strengthens faith in the rule of law in society. Therefore, an accurate understanding of the definition of public criminal prosecution is a kind of guarantee for the correct determination of the criminal law policy for a state. Today, the function of public criminal prosecution is represented on a fairly wide scale in the space of Georgian criminal procedure. This function needs to be further refined and established in a new way to make it more flexible and effective. For this, it is essential to have a clear legal definition of the concept of public criminal prosecution and accurately determine and manage the scope and terms of the prosecution.